2014
DOI: 10.1016/j.cmet.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of β Cell Glucagon-like Peptide-1 Signaling in Glucose Regulation and Response to Diabetes Drugs

Abstract: SUMMARY Glucagon-like peptide-1 (GLP-1), an insulinotropic peptide released from the intestine after eating, is essential for normal glucose tolerance (GT). To determine whether this effect is mediated directly by GLP-1 receptors (GLP1R) on islet β-cells, we developed mice with β-cell specific knockdown of Glp1r. β-cell Glp1r knockdown mice had impaired GT after intraperitoneal (IP) glucose, and did not secrete insulin in response to IP or intravenous GLP-1. However, they had normal GT after oral glucose, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
134
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 34 publications
17
134
3
Order By: Relevance
“…Hence, a tight relationship is suggested between the autonomic parasympathetic nerve activity and the action of endogenous GLP-1 on glucagon concentration. Our conclusion is also supported by recent data from the literature showing that the deletion of the GLP-1 receptor specifically in the β cells did not impair oral glucose induced insulin secretion in mice [45] further supporting the importance of GLP-1 receptors expressed in other than beta cells. Therefore, as we previously suggested, endogenous GLP-1 may control pancreatic endocrine secretions mainly through neural mechanisms [10,[46][47][48], whereas GLP-1 receptor agonists reaching high circulating concentrations of active agonist would control glycemia through a direct effect on β cells [49].…”
Section: Neuropathy Hamperssupporting
confidence: 89%
“…Hence, a tight relationship is suggested between the autonomic parasympathetic nerve activity and the action of endogenous GLP-1 on glucagon concentration. Our conclusion is also supported by recent data from the literature showing that the deletion of the GLP-1 receptor specifically in the β cells did not impair oral glucose induced insulin secretion in mice [45] further supporting the importance of GLP-1 receptors expressed in other than beta cells. Therefore, as we previously suggested, endogenous GLP-1 may control pancreatic endocrine secretions mainly through neural mechanisms [10,[46][47][48], whereas GLP-1 receptor agonists reaching high circulating concentrations of active agonist would control glycemia through a direct effect on β cells [49].…”
Section: Neuropathy Hamperssupporting
confidence: 89%
“…Octreotide reportedly suppresses plasma GLP-1 and GIP levels and improves early dumping syndrome [9,19]. Recently, Smith et al reported that the incretin effect of GLP-1 is not mediated by the GLP-1 receptor of the pancreatic β cells under normoglycemic conditions [20]. We also reported improvement of glycemic control by a GLP-1 receptor agonist through insulin-independent mechanisms [21].…”
Section: Case Presentationsupporting
confidence: 54%
“…Complicating this model further, GLP-1 can also act centrally to regulate food intake (Tang-Christensen et al 1996), energy expenditure (Lockie et al 2012), GI function (Seeley et al 2000) and importantly, glucose homeostasis (Knauf et al 2005, Gustavson et al 2008. However, in contrast to these studies, others suggest that the glucoregulatory effects of GLP-1 are primarily mediated by pancreatic GLP-1R activation (Lamont et al 2012, Smith et al 2014. Nonetheless, GLP-1 plays an important role in the regulation of metabolism and glucose homeostasis, and as a result, some of the latest drugs to come onto the market have aimed to exploit the GLP-1R signalling pathway.…”
Section: Gut Peptide Signalling In Regulating Glucose Metabolismmentioning
confidence: 99%
“…The effects of exenatide on food intake may be mediated by its central action, as exenatide-induced reductions in energy intake in humans have been associated with increased hypothalamic connectivity (Schlogl et al 2013), and intracerebroventricular injection of the GLP-1R antagonist, exendin-9, blocks the inhibitory effects of exenatide on energy intake in rodents (Kanoski et al 2011). However, the effects of exenatide on glucose regulation do not appear to be dependent on central GLP-1R activation (Lamont et al 2012), and evidence suggests that exenatide may exert its effects on glycaemia through direct action on the pancreas (Smith et al 2014). There has also been evidence that the anorexic effects of exenatide are mediated, at least in part, by the activation of GLP-1R expressed on peripheral vagal afferents.…”
Section: Glp-1r Agonistsmentioning
confidence: 99%
See 1 more Smart Citation